Canine antibody response to Lutzomyia longipalpis saliva in endemic area of visceral leishmaniasis. - Luís Fábio da Silva Batista; Vânia Lúcia Ribeiro da Matta; Thaise Yumie Tomokane; Acácio Duarte Pacheco; Fernando Tobias Silveira; Claudio Nazaretian Rossi; Mary Marcondes; Márcia Dalastra Laurenti (Revista da Sociedade Brasileira de Medicina Tropical, 2016)
Abstract: INTRODUCTION: Canine exposure to Lutzomyia longipalpis bites and the potential of Leishmania infantum transmissibility for the vector were evaluated. METHODS Immunoglobulin G (IgG) anti-Lu longipalpis saliva and -L. infantum, and blood parasite load were determined in dogs from endemic areas of visceral leishmaniasis. RESULTS Blood parasitism was similar between symptomatic and asymptomatic dogs. IgG anti-L. infantum was higher in symptomatic dogs, but IgG anti-Lu. longipalpis saliva was mostly observed in higher titers in asymptomatic dogs, indicating vector preference for feeding on asymptomatic dogs. CONCLUSIONS Our data suggest a pivotal role of asymptomatic dogs in L. infantum transmission in endemic areas.